PENURUNAN TINGKAT KEMATIAN IBU DAN BAYI BARU LAHIR BERBASIS PEMBERDAYAAN CIVIL SOCIETY DI KABUPATEN BANYUMAS - Ahmad Taufiq (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
The objective of the research is to analyze the descent of maternal and neonatal mortality rate program based on civil society empowerment in Banyumas   District, Central Java Province 2014. The research use qualitative model with several informants as sources of primary data. The data is taken by interviewing with  some informants,such as: Distric Team Leader of EMAS Banyumas Distric, Government Health Service of Banyumas Distric, CSSC Distric Banyumas, and civil society elements. Triangulation method is the best way to eliminate the fact contruction differences in the context of a certain study when collecting the data about the events and relationships of the various views. Through this technique the researchers also compared the findings with a variety of sources.The study found, firstly, to empower civil society in the  descent of maternal and neonatal mortality rate program based on civil society empowerment in Banyumas   District is to form  KIBBLA Forum  (Maternal, Child dan Neo-natal Health) as a  civil society forum in appreciation to critisize the health services by government; Secondly:  In context in civil society participation in the  descent of maternal and neonatal mortality rate implementation is to form FMM (Civil Soiety form). The forum use civil society connection is involved in that forum. The another form function is  the feed-back forum in health service program.